Menuju Masyarakat Sehat dan Berdaya : Pendekatan Terpadu dalam Meningkatkan Pengetahuan Kesehatan, Kesadaran Spiritual dan Jaringan Sosial - Fahdina Maulaya; Umi Faizatul Fadilah; Zunia Virasuli; Mamluatul Murivina; Abdul Karim (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
This study aims to evaluate the impact of the BKI student community service program on female students at the North Asrama An-Nahdhoh Putri Islamic Boarding School, with a focus on improving mental health, practical skills, and social networks. The method used in this study is a qualitative approach with a descriptive type, which collects data through in-depth interviews, observations, and documentation studies. The results of the study indicate that the community service program has succeeded in increasing female students' self-confidence, stress management skills, and better social relationships. In addition, extracurricular activities carried out every week have contributed significantly to the development of their practical skills. These findings emphasize the importance of community service programs in supporting the self-development of female students and creating a positive learning environment.